EXPLORING THE EXPERIENCES OF USING E-LEARNING MADRASAH IN TEACHING WRITING AT MADRASAH TSANAWIYAH NEGERI 1 KOTA BEKASI - Karunia Maratu Sholihah; Dini Hidayati (Universitas Panca Sakti Bekasi, 2022)
This study aims to describe the teachers’ experience in teaching writing to students with using E-Learning Madrasah application at MTs Negeri 1 Kota Bekasi. This was done to prescribe the teacher's instructional methods for teaching writing to the MTs Negeri 1 Kota Bekasi students in the familiarity of the teaching and learning process during and after covid-19 pandemic. This study used a qualitative methodology. Two English Teachers at MTs Negeri 1 Kota Bekasi served as the research subjects. Interviews and documentation were employed as research instrument. Data were collected through interviews with English teachers. The data analysis technique used in this study is an interactive model analysis adopted Miles and Huberman (2018), namely: reducing data, presenting data and concluding. The results showed that the teaching experience used by two teachers were the question-and-answer scheme. One solution to appliance the learning process is to be creative and innovative in learning. The methods used in distance learning are different from the face-to-face learning process. Distance learning during Covid-19 also made it a habit to use technology such as computers, laptop, internet and so on. The suggestion in this study has some suggestion namely: the teacher must use the E-learning features optimally in carrying out the teaching and learning process, the teachers must be creative and innovative in educating their students and also should have some new approach to help teaching writing in learning exercise, especially during and after pandemic circumstance